Adición del bagazo de caña en la técnica del bahareque como alternativa de construcción en casas Hogar de Cristo - Quinto Murillo, Yail Alberto (2025)
The bareque technique, also known as bahareque, is a construction method that has been used for centuries in various parts of the world. It is based on the interweaving of reeds or sticks covered with mud, resulting in a structure that combines sustainability and seismic resistance. In a global context, bahareque has proven to be an effective solution in rural regions and in indigenous communities that aim to enhance the high ecological characteristics of the material and reduce the cost of production and maintenance of social housing. In the specific context of the Hogar de Cristo Houses in Ecuador, the housing situation is critical. These institutions house people in vulnerable situations, including children, adolescents, older adults and people with disabilities. The current housing in these houses is usually precarious, built with low quality materials and without adequate techniques, which generates a series of habitability problems. The precariousness of the structures causes overcrowding, lack of ventilation and lighting, and high vulnerability to inclement weather, in addition to requiring constant maintenance and being prone to damage. Therefore, this method offers an economic and ecological alternative that uses locally available materials, reducing costs and environmental impact.